Pyogenic Liver Abscess Secondary to Sigmoid Diverticulitis: An Unusual Presentation - Muscat, Edward Paul Joseph (Case Rep Gastroenterol, 2020)
Pyogenic liver abscesses, despite being a rare complication of diverticulitis and inflammatory bowel disease, are potentially serious life-threatening pathologies. Diverticular diseases can lead to disruption of the colonic mucosal barrier and can serve as a route for bacterial infection via the portal venous system. This patient had such a delayed presentation due to his atypical symptoms; he developed large abscess formation, detected by computed tomography, eventually requiring an ultrasound-guided drain followed by a colonoscopy. The present report describes an elderly gentleman who developed a bacterial liver abscess due to seeding of a commensal organism caused by sigmoid diverticulitis.